Versatile Bulky N, N′, N′‐Substituted 1, 2‐Ethanediamine Ligands and Their Lithium, Aluminium, and Gallium Derivatives. Issue 5 (9th February 2017) - Kretschmer, Robert; Dehmel, Maximilian; Bodensteiner, Michael
Abstract : Sterically demanding N, N ′, N ′‐substituted 1, 2‐ethanediamine ligands have been prepared from commercially available starting materials by applying a facile one‐step procedure. These ligands offer advantages compared to known systems: a suppressed delocalization due to the saturated backbone inhibits a noninnocent behaviour and the low symmetry of the related metal complexes makes them potential candidates for asymmetric catalysis. The ligands are readily transformed into the corresponding lithium derivatives4, which in turn act as starting materials to access the corresponding aluminium and gallium dichlorides5 and6, respectively. In addition, deprotonation by Al(CH3 )3 gives rise to the related dimethylalane7 . All main‐group element compounds have been studied by means of single X‐ray crystallography and spectroscopic methods. Abstract : Adjustable ligands: A new class of bidentate ligands with adjustable steric demands and a saturated backbone was developed. In addition, a set of lithium, aluminium, and gallium derivatives has been prepared and investigated by means of single X‐ray crystallography and spectroscopic methods.